Effects of Child Life intervention on the symptom cluster of pain-anxiety-fatigue-sleep disturbance in children with acute leukemia undergoing chemotherapy - Rongrong Li; Xinyi Shen; Lin Zhang; Yuying Chan; Wenying Yao; Guanxun Zhang; Huiling Li (Elsevier, 2023)
Objective: This study aims to explore the application effect of Child Life intervention on pain, anxiety, fatigue, and sleep disturbance in children with acute leukemia. Methods: In a single-blinded, parallel-group randomized controlled trial, 96 children with acute leukemia were randomized to either the intervention group, which received Child Life intervention twice a week for 8 weeks, or the control group, which received routine care. Outcomes were evaluated at baseline and day 3 postintervention. Results: All of the participants completed the study. Compared with the control group, the intervention group showed a significant reduction in pain, anxiety, fatigue, and sleep disturbance (P ​< ​0.001). However, no significant differences were observed in the disorders of excessive somnolence. Conclusions: Child Life intervention can effectively improve pain, anxiety, fatigue, and sleep disturbance in children with acute leukemia undergoing chemotherapy. The results suggest that symptom cluster management intervention based on Child Life provided a promising approach for simultaneously treating multiple symptoms within a cluster.